Retirada de Opioides: uma revisão bibliográfica - MELLO, Andressa Piva de (2021)
Although opioids are useful for treating chronic pain due to producing analgesic as well as central nervous system depression effects, chronic activation of opioid receptors lead to dependence disorder, thus affecting individual’s health and social relationships. Dependence caused by opioid abuse is a challenge to health-care professionals. For this reason, this study aims at carrying out systematic data collection review, reflexive analysis, and up-to-date data review on the use of opioids, in addition to seeking alternatives for mitigating tolerance and addiction-related effects worldwide. In Brazil, there is insufficient epidemiological data; however, it is a well-known fact today that opioid analgesic drug use is high; the highest in South America. After the review, it remained clear that supervised withdrawal of opioids involving safe medications is necessary. In this sense, both methadone and buprenorphine are useful in the treatment of opioid withdrawal syndrome, decrease the symptons of desire and withdrawal, in addition to preventing the action of other opioids.